PENENTUAN SETTING PARAMETER OPTIMAL PADA PROSES PRODUKSI MI KERING MENGGUNAKAN METODE SHAININ DI CV. SUBUR ABADI, TULUNGAGUNG - Florencia Tandian; Eric Wibisono; Mochammad Arbi Hadiyat (Perpustakaan Universitas Surabaya, 2018)
Shainin is one of Design Experiment methods that can be used to get an optimal para meter setting. This method is a bit different than other Design Experiment methods. B y using Shainin, data are collected b ased on th e actual production process, so the data collection process does not disturb prod uction. This research was conducted in CV. Subur Ab adi that produces noodles. The production process is done throug h two production lines, where each li nes uses different drying machine, so the setting parameter will be different for each line. The characteristic of the noodle that will be optimized is the moisture content of dried noodles, with 9% -10% moisture content. After processing the data using Shainin method, the results showed that the moisture content of the dough affects the moisture content of dried noodles. On the north machine, parameters setting that affect the moisture content are dough moisture content, actual temperature and boiler pressu re. On the south mac hine, parameters setting that affect the moisture content are dough moisture content and boiler pressure. The optimal parameter setting for the north machine are actual temperature of 84.8 to 85 oC, boiler pressure of 7.6 to 7.7 kg/cm2, and dough moisture content of 31.3 to 31.4%. For the south machine, the optimal parameter setting are boiler pressure of 7.8 to 8 kg/cm2 and dough moisture content of 31,05 to 31,15%.